Perfil de expressão diferencial de proteínas associadas às alterações pós-colheita em maçãs cv. Gala, clone Baigent. - Moura, Renata Silva (2011)
The apple (Malusxdomestica), from Europe and Asia, belongs to the family Rosaceae, sub-family pomaceas. The apple is a temperate fruit of commercial importance, especially in its fresh state. Among the main apple cultivars grown in Brazil, we are Fuji and Gala, as the most preferred by consumers in Brazil, produced fruits with good sensory characteristics such as appearance, crisp and juicy pulp. However, these attributes are quickly lost during storage under refrigeration (AR). Among the main problems encountered during cold storage, are the decrease in firmness and the occurrence of mealy pulp. Several studies have shown that these physiological disorders are related to ethylene, and its mechanisms have not yet been elucidated. In order to seek further explanation of the molecular mechanisms of interaction of these events with the ethylene, this work proposes a comprehensive analysis of the system using proteomics to study methods. In this context, the objective was to identify and characterize differentially expressed proteins during storage, linking them to the action of ethylene and with changes in fruits of cv. Gala - Baigent clone. In the gels from two-dimensional electrophoresis were detected using the PDQuest program, 565 spots in the sample of apples at 8 months of RA in fruit treated with MCP-1, 452 sample spots for eight months without an RA in fruits - MCP, 348 spots corresponding to sample the fruits at harvest. In a quantitative analysis, when comparing treatments with and without 1-MCP, and considering only the proteins present in both treatments, 120 of them increased or decreased in intensity. Moreover, it was found that 62 spots were detected only in samples treated or not treated with the MCP-1, 160 spots were detected only in samples corresponding to the crop or the samples treated with 1-MCP, and 80 spots were detected only in samples corresponding to the collection or to samples not treated with 1-MCP. The identification and study of their functions are the next steps in the work.